Exploring the Relationship Between Corporate Social Responsibility and Corporate Sustainability within the Food and Beverage Industry - Fatunnisa, Hani; Hamdani, Nizar Alam; Permana, Intan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The objective of this paper is to examine the relationship between corporate social responsibility and corporate sustainability. Moreover, the paper examines how dimensions correlate with corporate sustainability. This research uses quantitative research methods. The data analysis technique used is simple linier regression with the help of SPSS 29. Based on the results of the research conducted, there is a relathionship between corporate social responbility and corporate sustainability. The result of this study support the result of previous studies that by using a corporate social responbility approach, companies will not only get economic benefits, but will also get social benefits. Thus the sustainability of the companies can take place well. It is concluded that companies with corporate social responsibility approach, the company not only gains economic benefits but gains social benefits. Business continuity can last well over a long period of time. This research has benefits so that business owners in various industries continue to carry out environment responsibility for business sustainability. In addition, the study also finds a positive relationship between corporate social responsibility and corporate sustainability. The analysis of the paper is based on survey responses from 44 stakeholders (i.e.,  shareholders, employees, and customers) within the food and beverage industry.